TEACHING READINESS OF OFFICE ADMINISTRATION EDUCATION STUDENTS: THE IMPACT OF MICROTEACHING AND INTEREST IN TEACHING - Putri, Chintya Adinda; Eryanto, Henry; Rachmadania, Rizki Firdausi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
This study aims to investigate the effect of Microteaching Learning and Interest in Becoming a Teacher on Teaching Readiness in Office Administration Education Students at Universitas Negeri Jakarta. By using quantitative approach where surveys are the method that helps this research. All active students from the Office Administration Education study program at Universitas Negeri Jakarta, totaling 173 students, were involved in the survey process. For sampling, this study applied proportionate stratified random sampling with a margin of error of 5%, so that 121 students were generated as the sample size for this study. SmartPLS version 4.0 is the software that helps the process of research data analysis techniques. As a result, the researcher found that, (1) Microteaching learning positively affects student teaching readiness, (2) Interest in Becoming a Teacher positively affects student teaching readiness significantly, and (3) Microteaching Learning and Interest in Becoming a Teacher simultaneously have a positive effect on student teaching readiness significantly.